Subunit structure of paired helical filaments in Alzheimer's disease (The Rockefeller University Press, 1985)
The neurofibrillary tangles that occur in the brain in cases of senile dementia of the Alzheimer type contain a distinctive type of filament, the paired helical filament (PHF). We have developed a method for isolating the tangles postmortem in sufficient yield for structural study of PHFs by electron microscopy of negatively stained and shadowed preparations. This material shows the characteristic helical structure seen in sectioned embedded material. In addition, two striking fragmentation patterns are observed. (a) Some filaments show sharp transverse breaks at apparently random positions along the filament. (b) In a few PHFs one strand is missing for a variable length, whereas the other appears to maintain its structural integrity. The shadowed specimens show the PHF to be wound in a left-handed manner. These observations indicate that the PHF consists of subunits of very limited axial extent arranged along two left-handed helical strands. The visualization of the substructure within the PHFs is rather variable and a model building approach has therefore been adopted, which has allowed the main features seen in the images to be interpreted. The subunit appears to have at least two domains in a radial direction and an axial extent of less than 5 nm. The whole structure can best be described as a twisted ribbon and indeed alkali treatment does untwist PHFs to give flat ribbons. The nature of the proposed model makes it most unlikely that the PHF is formed by a simple collapse of normal cytoskeletal elements, such as neurofilaments.